The digital transformation of banking - Sucubasi, Bilal; Bojadzvievska Danevska, Andrijana; Dimitrieska, Savica; Parnardzieva Stanoevska, Elena (Routledge focus on economics and finance, 2025)
The banking sector is evolving rapidly due to technological advancements, regulatory changes, and shifting customer expectations. This book addresses these changes by comprehensively analysing key areas where technology intersects with banking.It provides a detailed and insightful examination of how technological advances have historically impacted and continue to shape the banking sector. It offers an up-to-date analysis of emerging trends such as Central Bank Digital Currencies (CBDCs) and artificial intelligence (AI), helping stakeholders make informed decisions. It presents practical insights and strategies for bank marketing and risk management in the contemporary environment. Further, it underscores current and future trends and highlights the opportunities, ethical considerations, and challenges when banking and advanced technology meet. The book employs frameworks and models applicable across multiple disciplines, for example, using risk management frameworks that incorporate both financial and technological risks, making the analysis more holistic.By engaging with a wide range of stakeholders, including reports from policymakers, financial institutions, consultancies, and technology providers, the research addresses practical concerns and is grounded in real-world challenges and opportunities. Finally, the use of case studies from different countries and industries provides practical examples that illustrate how interdisciplinary concepts are applied in real-world scenarios. This method helps bridge theoretical knowledge with practical applications. The book proposes specific policy recommendations based on the analysis of CBDCs and risk management practices, and the research findings and insights contained in it are accessible and actionable for a broad audience, including academics, researchers, and students, as well as policymakers, financial institutions, and technology providers.